2018
DOI: 10.3389/fpubh.2018.00321
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Care Model With Implementation Roadmap to Improve Chlamydia trachomatis Management and Control in India

Abstract: Chlamydia trachomatis is the world's most prevalent bacterial Sexually Transmitted infection (STI). It is associated with a wide range of health consequences and sequelae in both the short and long term. Enhanced control of urogenital C. trachomatis infection is particularly important in low- and middle-income countries such as India, where most of the burden goes unnoticed and where limited systematic data is available to gauge the current situation. The World Health Organization (WHO) recently issued its lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…As previously mentioned, these four studied non-viral STIs continue to have an impact on maternal health and pregnancy outcomes in various countries [55,56]. The approach to diagnosis and managing them should align with global STI eradication strategies, depending on the available resources and epidemiological information per country [56,57]. In this low-resource setting, where antenatal and health care is limited, and maternal and infant morbidity is high, it is important to understand the burden of (curable) pathogens that might cause long-term impact on female reproductive health beyond pregnancy, causing, for instance, ectopic pregnancy or successive infertility [57,58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously mentioned, these four studied non-viral STIs continue to have an impact on maternal health and pregnancy outcomes in various countries [55,56]. The approach to diagnosis and managing them should align with global STI eradication strategies, depending on the available resources and epidemiological information per country [56,57]. In this low-resource setting, where antenatal and health care is limited, and maternal and infant morbidity is high, it is important to understand the burden of (curable) pathogens that might cause long-term impact on female reproductive health beyond pregnancy, causing, for instance, ectopic pregnancy or successive infertility [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…The approach to diagnosis and managing them should align with global STI eradication strategies, depending on the available resources and epidemiological information per country [56,57]. In this low-resource setting, where antenatal and health care is limited, and maternal and infant morbidity is high, it is important to understand the burden of (curable) pathogens that might cause long-term impact on female reproductive health beyond pregnancy, causing, for instance, ectopic pregnancy or successive infertility [57,58]. Establishing the burden of these pathogens through epidemiological biobank data-driven research in (a)symptomatic populations is an important first step for the management and control of the burden of pathogen-related diseases in communities, including in Pemba Island [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 , 30 , 47 In SSA, where antenatal and healthcare are limited and maternal and infant morbidity is high, it is important to understand the burden of STIs and its impact on female reproductive health, maternal health and neonatal consequences. 48 , 49 Most recently, in developing countries because of STIs, the WHO reported a stillbirth rate of 25.6 per 1000 births in 2009 and a neonatal mortality rate of 28 per 1000 births in 2015 compared to 2.4 and 2.0 in developed countries, respectively. 50 Recently published data showed that in numerous regions of the world antenatal screening for STIs is not regularly practiced, particularly in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, large-scale screening programs for patients at risk are recommended by countries. (Fox, Dobler, Marais, & Denholm, 2017) Since 70-80% of C. trachomatis infections go unrecognized (Twohig, 2013), prolonged infection may raise the risk for pelvic inflammatory illness, tubal factor associated infertility, and ectopic pregnancy (Lawton et al, 2004;Thomas et al, 2018). All these sequelae can worsen tubal disease, reducing the possibility of conception after tubal flushing.…”
Section: Introductionmentioning
confidence: 99%